An unusual presentation of component separation after percutaneous transmural arterial bypass (PTAB) - Kirby Derek, DO; Maraya Camazine, MD; Todd R. Vogel, MD, MPH (Journal of Vascular Surgery Cases and Innovative Techniques)
This case report details a percutaneous transmural arterial bypass for a long (20-25 cm) occlusive lesion causing intermittent rest pain in a patient with multiple comorbid conditions. Initial lower extremity intervention was without complication; however, 1 month postoperatively, the patient presented acutely with severe rest pain, a diminished ankle-brachial index of 0.35, and a swollen extremity. Computed tomography angiography findings demonstrated component separation, which was subsequently repaired with placement of a covered stent. Symptoms immediately improved, and the patient was discharged on postoperative day one. This case report illustrates methods of managing the unusual complication of component separation, which presented as acute limb ischemia.